Produksi Ayam Broiler Organik Kaya Protein Untuk Meningkatkan Imunitas Tubuh Masa Pandemic Covid-19 - Zulkarnain, Deki; Aku, Achmad Selamet; Pagala, Muhammad Amrullah; Tasse, andi Murlina; Malesi, La; Has, Hamdan (Vokasi Universitas Halu Oleo, 2021)
The Thematic Real Work Lecture (KKN-T) Halu Oleo University in Matabubu Village, Poasia District, Kendari City, Southeast Sulawesi, has the aim of activities to increase body immunity during the Covid-19 pandemic and increase community motivation to manage and raise public awareness of the importance of using masks during the COVID-19 pandemic, especially for poultry farmers by providing community empowerment efforts in development in the integrated livestock sector, program activities carried out by Thematic KKN Students in the form of material delivery to breeders, counseling to breeders and training and community assistance in making fertilizer compost. However, the presence of the covid-19 virus limits Thematic KKN students to be more with the community with association activities.Â